APLIKASI TEKNOLOGI PENGINDERAAN JARAK JAUH UNTUK MENGIDENTIFIKASI HEAT ISLAND (â€œPULAU PANASâ€) DI KOTA PEKANBARU - Ikhwan, Muhammad; Hadinoto, Hadinoto (Wahana Forestra: Jurnal Kehutanan, 2015)
The increasingly development in Pekanbaru city caused the environmental change. This condition also affected to the increased of surface temperature on the urban area of Pekanbaru City. The increasing of surface temperature will lead the increasing of air temperature which could impact to the uncomfortable activity in Pekanbaru City. The high air temperature in urban areas is caused by increasing built-up areas and declining green open space. Green open space should be built to lower air temperature and to create a comfortable micro climate. Green open space should be developed at locations with high air temperature to reach its efficiency. The research was aimed to identify the phenomena of Heat Island in Kota Pekanbaru. The processing satellite image data of band 6 of Landat 7 ETM+ was conducted to produce the distribution of surface temperature in Pekanbaru City. The results shows that, the surface temperature of the urban area is higher than the green open space area, especially for residence area, road, office building area and bare land. This condition indicates that the phenomena of Heat Island accurs in Pekanbaru City.